Regional offices in the new NHS: an analysis of the effects and significance of recent changes - Dopson, S; Locock, L; Stewart, R (Blackwell Publishers, 1999)
This article reports on a two-year, multi-method, qualitative study in two regional offices in the UK National Health Service of the changing role of the regional tier from the autumn of 1994. The nature of the changes from fourteen semiautonomous regional health authorities to eight regional offices of the NHS Executive, whose staff became civil servants, are described together with the way this reorganization changed the role and relationships of NHS Executive HQ, the regional offices and the field. By the end of our research in the autumn of 1996, the change from regional health authority to regional office had gone well in the two regional offices studied; they had become smaller organizations, had established closer working with HQ and believed they had more influence over policy, while retaining good relations with health authorities. Emerging issues from the changes and some of their implications are discussed, particularly the pressures towards greater centralization and the particular forms that these have taken, despite the aim, and in part the achievement, of greater devolution, and the cultural differences between the NHS and the civil service. We conclude by assessing what the future holds for regional offices, in the light of the recent NHS White Paper (Secretary of State for Health 1997)